Two novel mutations in seven Czech and Slovak kindreds with familial neurohypophyseal diabetes insipidus-benefit of genetic testing - Hrčková, Gabriela; Jankó, Viktor; Kytnarová, Jitka; Čižmárová, Michaela; Tesařová, Markéta; Košťálová, Ľudmila; Virgová, Daniela; Dallos, Tomáš; Hána, Václav; Lebl, Jan; Zeman, Jiří; Kovács, László (European journal of pediatrics, 2016)
UNLABELLED: Familial neurohypophyseal diabetes insipidus (FNDI) is a rare hereditary disorder with unknown prevalence characterized by arginine-vasopressin hormone (AVP) deficiency resulting in polyuria and polydipsia from early childhood. We report the clinical manifestation and genetic test results in seven unrelated kindreds of Czech or Slovak origin with FNDI phenotype. The age of the sign outset ranged from 2 to 17 years with remarkable interfamilial and intrafamilial variability. Inconclusive result of the fluid deprivation test in three children aged 7 and 17 years old might cause misdiagnosis; however, the AVP gene analysis confirmed the FNDI. The seven families segregated together five different mutations, two of them were novel (c.164C > A, c.298G > C). In addition, DNA analysis proved mutation carrier status in one asymptomatic 1-year-old infant. CONCLUSIONS: The present study together with previously published data identified 38 individuals with FNDI in the studied population of 16 million which predicts a disease prevalence of 1:450,000 for the Central European region. The paper underscores that diagnostic water deprivation test may be inconclusive in polyuric children with partial diabetes insipidus and points to the clinical importance and feasibility of molecular genetic testing for AVP gene mutations in the proband and her/his first degree relatives. WHAT IS KNOWN: • At least 70 different mutations were reported to date in about 100 families with neurohypophyseal diabetes insipidus (FNDI), and new mutations appear sporadically. What is New: • Two novel mutations of the AVP gene are reported • The importance of molecular testing in children with polyuria and inconclusive water deprivation test is emphasized.
Keywords: mutace; dospělí; Genetic Testing; heterozygot; Magnetic Resonance Imaging; centrální diabetes insipidus; Base Sequence; Arginine Vasopressin; Female; Infant; věk při počátku nemoci; rodina; Diabetes Insipidus, Neurogenic; dítě; Prevalence; Adult; ženské pohlaví; mladý dospělý; Adolescent; Slovakia; lidé; Heterozygote; magnetická rezonanční tomografie; polydipsie; arginin vasopresin; Mutation; Polydipsia; Aged, 80 and over; mozek; Polyuria; prevalence; Male; kojenec; Aged; Brain; Czech Republic; Young Adult; sekvence nukleotidů; polyurie; genetické testování; Family; Česká republika; lidé středního věku; Child; senioři nad 80 let; Slovenská republika; senioři; mužské pohlaví; Age of Onset; Middle Aged; mladiství; Humans